Implementasi Pembelajaran Kitab Taisirul Kholaq Dalam Pembentukan Akhlak Santri di Asrama Al-Kautsar PP. Darul Ulum Jombang - Santoso, Setia Budi; M, Mufaizah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research focuses on moral learning for students at the Al-Kautsar PP Dormitory. Darul Ulum Jombang using the Taisirul Kholaq Book as teaching material. The aim of this research is to analyze the teaching of the Taisirul Kholaq Book in the Al-Kautsar Dormitory and show the importance of the role of caregivers, ustadz and coaches in shaping the morals of students. This research also identifies the driving and inhibiting factors in the formation of santri morals. The observation method is used as a way of collecting data through systematic observation and recording of the phenomena being investigated. The interview method was also used to obtain in-depth information from respondents about the process of learning the Book of Taisirul Kholaq in forming the morals of students at the Al-Kautsar Dormitory. The collected data was analyzed using the analysis method described by Miles and Huberman, through data reduction, data display, and conclusion drawing/verification activities. The results of the research show that learning about santri morals at the Al-Kautsar Dormitory focuses on teaching the Book of Taisirul Kholaq and is held regularly in one class for all santriwan and female students. The role of caregivers, ustadz and coaches is very important in shaping the morals of students, especially in Islamic boarding school environments where they act as substitute parents. Praying before studying is a practice implemented by ustadz and supervisors to shape the morals of students, with a significant impact. Encouraging factors such as role models, parents and the environment have a positive influence on the formation of students' morals, while inhibiting factors such as background and negative influences can hinder the process of forming good morals.